ORTHODONTIC TREATMENT NEED AT A PUBLIC SPECIALIZED DENTAL CARE CENTER OF SOBRAL - CEARÁ - Adeodato, Maria Vilma; Nobre Chaves, Filipe; de Barros Silva, Paulo Goberlânio; Santamaria Júnior, Milton; Cristina Valdrighi, Heloísa; Scudeler Vedovello, Silvia Amélia (Cadernos ESP, 2021)
The aim of this paper was determine the normative orthodontic treatment need of patients treated at a public Specialized Dental Care Center, seeking to correlate these characteristics with sex, type of dentition, age and data of the cities of the patients. Were evaluated 438 orthodontic documentations, of patients aged 6 to 12 years, adopting the criteria established by Index of Orthodontic Treatment Need (IOTN). Data were expressed in the form of absolute and percentage frequency and inferentially compared using the Chi-square test or Fisher´s test, considered of 95% confidence interval. It was observed that 72.6% of patients showed great need for orthodontic treatment. There was no statistically significant association between index of orthodontic treatment need with the dentition (p = 0.059), sex (p = 0.998), age (p=0.253), HDI (p = 0.749) and coverage rate of oral health teams of the cities of the patient (p = 0.898). It was concluded that most patients have great need for orthodontic treatment and this need isn´t influenced by sociodemographic factors.